The Real Impact of the Coronavirus Disease 2019 (covid-19) on the Pregnancy Outcome - Ana Katherine Gonçalves
Abstract The COVID-19 outbreak is increasing around the world in the number of cases, deaths, and affected countries. Currently, the knowledge regarding the clinical impact of COVID-19 on maternal, fetal, and placental aspects of pregnancy is minimal. Although the elderly and men were the most affected population, in previous situations, such as the 2009 H1N1 influenza pandemic and the Ebola epidemic, pregnant women were more likely to develop complications than nonpregnant women. There are unanswered questions speciﬁc to pregnant women, such as whether pregnant women are more severely affected and whether intrauterine transmission occurs. Additional information is needed to inform key decisions, such as whether pregnant health care workers should receive special consideration, whether to separate infected mothers and their new borns, and whether it is safe for infected women to breastfeed.